The Influence of Compensation and Perceived Organizational Support on Employee Engagement with Job Satisfaction as an Intervening Variable at PT MNC Sekuritas Jakarta Head Office - Izzatinisa, Izzatinisa; Budiono, Nur Aktif (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nowadays, companies that provide community investment are starting to mushroom. To compete with competitors, MNC Sekuritas tries to retain the best human resources and encourage these resources to be more efficient and effective in their work. The research aims to determine the influence of Compensation and Perceived Organizational Support on Employee Engagement with Job Satisfaction as an intervening variable. The research population was all permanent employees of the PT MNC Sekuritas Jakarta head office with a sample of 105 respondents. The research uses a quantitative approach with survey methods. Analysis of SEM-PLS data using SmartPLS 3 software. The results of the research show that compensation does not have a significant influence on Employee Engagement, but has a significant influence on Job Satisfaction. Perceived Organizational Support has a significant influence on Job Satisfaction and Employee Engagement. It was also found that Job Satisfaction has a significant influence on Employee Engagement. Compensation and Perceived Organizational Support through Job Satisfaction have a significant influence on Employee Engagement.